A correlation study between hydrogen-bonded network and gelation ability of three galactose derivatives1. Issue 17 (7th May 2015) - Mukherjee, Somnath; Rama Krishna, G.; Mukhopadhyay, Balaram; Malla Reddy, C.
<x xml:space="preserve">Abstract</x> The hydrogen bonding network in the crystals of the three saccharides was correlated with their gelling ability or inability, and unexpectedly, a 2D hydrogen-bonded system was found to show efficient gelation, whereas a 1D hydrogen bonding system was a nongelator.